2023
DOI: 10.1001/jamasurg.2023.4154
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Free Discharge After Pancreatic Resection Through a Learning Health System Paradigm

Artem Boyev,
Anish J. Jain,
Timothy E. Newhook
et al.

Abstract: ImportancePostoperative opioid overprescribing leads to persistent opioid use and excess pills at risk for misuse and diversion. A learning health system paradigm using risk-stratified pancreatectomy clinical pathways (RSPCPs) may lead to reduction in inpatient and discharge opioid volume.ObjectiveTo analyze the outcomes of 2 iterative RSPCP updates on inpatient and discharge opioid volumes.Design, Setting, and ParticipantsThis cohort study included 832 consecutive adult patients at an urban comprehensive canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…[84][85][86] In addition to improved short-term outcomes and costs, we have reported significant opioid reduction after pancreatectomy and gastrectomy: the majority of patients do not require an opioid prescription at the time of discharge. 85,87 MIS has consistently demonstrated a reduction in opioid use across various operations compared to open approaches, as reported in several studies. [88][89][90][91] However, limited data exist regarding opioid use after oncologic gastrectomy or pancreatectomy.…”
Section: Opioid Epidemic In the United States And Opioid Reduction By...mentioning
confidence: 54%
See 1 more Smart Citation
“…[84][85][86] In addition to improved short-term outcomes and costs, we have reported significant opioid reduction after pancreatectomy and gastrectomy: the majority of patients do not require an opioid prescription at the time of discharge. 85,87 MIS has consistently demonstrated a reduction in opioid use across various operations compared to open approaches, as reported in several studies. [88][89][90][91] However, limited data exist regarding opioid use after oncologic gastrectomy or pancreatectomy.…”
Section: Opioid Epidemic In the United States And Opioid Reduction By...mentioning
confidence: 54%
“… 84 , 85 , 86 In addition to improved short‐term outcomes and costs, we have reported significant opioid reduction after pancreatectomy and gastrectomy: the majority of patients do not require an opioid prescription at the time of discharge. 85 , 87 …”
Section: Robotic Surgery For Cancermentioning
confidence: 99%
“…It is less likely to help with other causes of postoperative pain. Boyev et al 49 performed a cohort study of 832 patients getting pancreatic resections and demonstrated that administering muscle relaxants as part of the postoperative bundle in addition to acetaminophen and NSAIDs helped decrease the inpatient opioid volume by half and the median opioid volume at discharge to 0. These findings suggest that when muscle relaxants are used appropriately in major abdominal procedures in addition to the standard nonopioid postoperative bundle, it can help reduce inpatient opioid use and increase the number of patients able to be discharged opioid free.…”
Section: Discussionmentioning
confidence: 99%